2020
DOI: 10.1016/j.jort.2020.100329
|View full text |Cite
|
Sign up to set email alerts
|

City tourism pre- and post-covid-19 pandemic – Messages to take home for climate change adaptation and mitigation?

Abstract: The paper presents the status quo on climate change impacts on city tourism in Austria describing the impacts by air travel and a short stay on the greenhouse gas emissions and the changing conditions in the city. For Austrian cities, depending on location and topography, heavy rainfall events, storms and heat waves in particular could become increasingly relevant in the tourism context. For medium-sized and large cities, heat is the most frequently discussed topic in connection with possible adaptation potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 6 publications
(8 reference statements)
1
37
0
6
Order By: Relevance
“…There are limited studies in the recent pandemic literature specific to urban or rural tourism. Some scholars have suggested that the suspension of tourism during COVID-19 has provided new incentives to revitalize urban tourism (Jiricka-Pürrer et al , 2020), especially in relation to adapting to climate change. Scholars also acknowledge that the impact of the normalization of the pandemic on the tourism system (Ateljevic, 2020) may have implications for regenerative agriculture and transformation tourism.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are limited studies in the recent pandemic literature specific to urban or rural tourism. Some scholars have suggested that the suspension of tourism during COVID-19 has provided new incentives to revitalize urban tourism (Jiricka-Pürrer et al , 2020), especially in relation to adapting to climate change. Scholars also acknowledge that the impact of the normalization of the pandemic on the tourism system (Ateljevic, 2020) may have implications for regenerative agriculture and transformation tourism.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Insurance and subsidy programs for employees; support the survival of the hotel and airline industry [3,[13][14][15][16][17] Play the function of the informal sector Cooperation between the informal sector and government departments; provide microfinance; provide bank insurance [18,19] Prioritize actions Quick response to the tourism industry in crisis [13,15] Formulate public policy Prohibit or restrict the arrival of giant cruise ships and promote the development of small cruise ships; issue policies to support the aviation and hotel industry; government supervision of policy implementation [12,20,21] Table 5. Government crisis management: after the crisis.…”
Section: Financial Supportmentioning
confidence: 99%
“…Mindfulness; attitudes of tourists to hosts; social responsibility and civic values; understanding of sustainability; attitudes to sustainable products and destinations [13,19] On the other hand, scholars have found that in general, COVID-19 will prompt enough individuals, companies, and governments to adopt new ways of thinking, behavior, and operations that are more consistent with the sustainable development goals (like [13,32]). Therefore, they further proposed that if the tourism industry can take the expansion and stimulation of global awareness as the important value of the products and experiences it provides, then this function of the tourism industry should be strengthened (like [33,34]).…”
Section: Angle Example Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…The novel coronavirus disease has been taking a devastating toll from all over the world. This pandemic and climate change already have been impacted on several sectors in our life such as tourism (Jiricka-Pürrer et al 2020), agriculture and food security (Rasul, 2021), air travel restrictions (Kallbekken and Saelen, 2021), public health (Pascal et al 2021), mental health (Marazziti et al 2021), energy and its management , human behavior changes (Botzen et al 2021 andNakajima et al 2021), waste respirator processing system (Zhao and You, 2021) and their different strategic management (Rahman et al 2021). Therefore, a very strong relationship between both climate change and COVID-19 pandemic, and the global food security particularly in developing states (Hickey and Unwin, 2020).…”
Section: Introductionmentioning
confidence: 99%